Channelling eggshell waste to valuable and utilizable products: A comprehensive review. (December 2020) - Waheed, Marium; Yousaf, Muhammad; Shehzad, Aamir; Inam-Ur-Raheem, Muhammad; Khan, Muhammad Kashif Iqbal; Khan, Moazzam Rafiq; Ahmad, Naveed; Abdullah,; Aadil, Rana Muhammad
Abstract: Background: Owing to increased egg consumption globally, a corresponding surge of about 18% in egg production has been recorded during the last decade as reported by WATT Global Media's Executive Guide to World Poultry Trends. Up till 2017, global egg production has hit 80-million metric-ton mark with China, USA and India, being the leading egg-producing countries contributing their share of 458, 109 and 95 billion eggs per annum, respectively. Global egg production for the year 2018 was 78 million metric tons, contributing approximately 8.58 million metric ton of eggshells which are being discarded mostly as waste. This calcium-rich commodity is dumped into landfills, leading to various environmental issues, and therefore should be tackled properly. Scope and approach: Eggshells are obtained from egg processing plants, egg stations, chicken hatcheries, industries and homes in millions of tonnes and can be employed in a myriad of fields. The following review article provides a brief insight into various applications of eggshells in our society, such as their use in medicinal supplements, bone graft substitute and denture base. Eggshells can also be employed in constructing floor tiles and in cement to enhance compressive strength. Other diverse applications of eggshell may include animal feed, plant fertiliser, batteries, inkjet printers, biodiesel production and removal of heavy metals from soil and water. Key findings and conclusion: The increasing urbanisation and industrialization with amplified waste generation have wreaked havoc on our climate; thus, making it necessary to take certain extravagant measures to ensure the safety and sustainability of our planet. Graphical abstract: Image 1 Highlights: Egg consumption is expected to increase from 7951.8 million dozens in 2019 to over 8000 million dozens in 2020. USDA projects consumption statistics to reach up to 8917 million dozens by 2028. Leading eggshell producing countries are China, USA and India. It is the need of hour to convert waste into useful commodities for sustainable development.